2021
DOI: 10.3390/v13061102
|View full text |Cite
|
Sign up to set email alerts
|

HERC5 and the ISGylation Pathway: Critical Modulators of the Antiviral Immune Response

Abstract: Mammalian cells have developed an elaborate network of immunoproteins that serve to identify and combat viral pathogens. Interferon-stimulated gene 15 (ISG15) is a 15.2 kDa tandem ubiquitin-like protein (UBL) that is used by specific E1–E2–E3 ubiquitin cascade enzymes to interfere with the activity of viral proteins. Recent biochemical studies have demonstrated how the E3 ligase HECT and RCC1-containing protein 5 (HERC5) regulates ISG15 signaling in response to hepatitis C (HCV), influenza-A (IAV), human immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 145 publications
(177 reference statements)
2
29
0
Order By: Relevance
“…In addition, HERC5, RSAD2, and DDX60 are all interferon induced-genes, which play important roles in antiviral response (36)(37)(38)(39). Consistent with our findings, recent studies revealed that the expression level of RSAD2 was markedly increased in the SLE samples compared with controls, which may act as a potential biomarker gene and therapeutic target for the treatment of SLE (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…In addition, HERC5, RSAD2, and DDX60 are all interferon induced-genes, which play important roles in antiviral response (36)(37)(38)(39). Consistent with our findings, recent studies revealed that the expression level of RSAD2 was markedly increased in the SLE samples compared with controls, which may act as a potential biomarker gene and therapeutic target for the treatment of SLE (40,41).…”
Section: Discussionsupporting
confidence: 91%
“…In the group of patients with moderate clinical conditions over uninfected control individuals, we observed the expansion of a few sets of biologically grouped genes, with the greatest increase in groups of genes related to cell proliferation. Moreover, the second most represented group of genes was related to antiviral activity (156)(157)(158). On the other hand, in severe over mild cases, the MSCs response was completely different, as they assumed a genotype compatible with a multipurpose protective cell population.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms have been demonstrated through which free ISG15 and ISGylation possibly contribute to the etiology of human ailments. ISG15 is involved through marking proteins for degradation, antagonizing protein degradation (stabilizing proteins), affecting protein localization, preventing the formation of protein complexes, or regulating immune response(s) [96,126,[136][137][138][139][140][141][142][143][144][145][146][147][148][149][150]. In the current review, we shall focus on the role of the ISG15 pathway in human diseases through protein degradation.…”
Section: The Isg15 Pathway In Human Diseasesmentioning
confidence: 99%
“…After two decades, Ketscher et al reported that inhibition of USP18 deISGylation activity enhances ISGylation and viral resistance [198], supporting the earlier observations by Haas et al Several groups have now endorsed an anti-viral function of ISG15 and ISGylation against murine Gammaherpesvirus, Influenza A and B viruses (IAV), Sindbis virus (SNV), Vaccinia virus, Herpes simplex virus 1 (HSV-1), Chikungunya virus, murine Norovirus, Ebola virus, Dengue virus, and West Nile virus in cell culture, animal, and human studies [96,126,136,142,146,147]. Whether ISG15/ISGylation plays a role in establishing anti-viral immunity against the SARS-CoV-2 virus is unknown; however, there are literature reports implicating the same [145,199,200].…”
Section: Isg15 In Viral and Bacterial Pathogenesismentioning
confidence: 99%